2014
DOI: 10.1109/tgrs.2013.2258162
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Multitemporal and Hyperspectral Vegetation Canopy Bidirectional Reflectance Using Detailed Virtual 3-D Canopy Models

Abstract: The influence of plant and canopy architecture on canopy bidirectional reflectance and the BRDF is subject of this study. To understand BRDF-influenced reflectance signals, this influence must be identified and quantified, which requires detailed knowledge concerning the structure and BRDF of the observed canopies. BRDF measurements of in-situ canopies are time-consuming and depend on the availability of a field goniometer. In contrast to field measurements, computer based simulations of the canopy BRDF offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…Thus, they are closer to the hotspot feature apparent for anisotropic surfaces and show a higher reflectance. These results aligns with other studies, which also found that the relative influence of the view angle on the apparent reflection of vegetation in the VIS is considerable higher than in the NIR, were light is scattered within the canopy Küster et al, 2014;Sandmeier et al, 1999;Schläpfer et al, 2015).…”
Section: Influence On the Apparent Reflectionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, they are closer to the hotspot feature apparent for anisotropic surfaces and show a higher reflectance. These results aligns with other studies, which also found that the relative influence of the view angle on the apparent reflection of vegetation in the VIS is considerable higher than in the NIR, were light is scattered within the canopy Küster et al, 2014;Sandmeier et al, 1999;Schläpfer et al, 2015).…”
Section: Influence On the Apparent Reflectionsupporting
confidence: 92%
“…Additionally, they show a hotspot feature directed towards the direct incidence irradiance, which is more pronounced in the visible region (VIS) than in the near infrared region (NIR). Additionally, at nadir they show a local maximum in the VIS and an local minimum at the NIR (Gerstl and Simmer, 1986;Küster et al, 2014).…”
Section: Angular Scattering Effects Of Vegetationmentioning
confidence: 99%
“…The approach uses a tightly-coupled system of crop growth and crop radiative transfer models to derive spatio-temporal fields of crop parameters through iterative ensemble analysis [57]. A model for the realistic simulation of the hyperspectral and multiangular reflectance response of virtual 3D cereal canopies has also been implemented in the framework of EnMAP [58].…”
Section: Development Of the Enmap Science Planmentioning
confidence: 99%
“…In an inverse conception, illuminated leaves can be seen as light sources emitting a distorted light spectrum. High-performance simulation techniques and hyperspectral ray-tracing methods are requirements to exploit the full potential of the sensor signal [21] and at the same time for the generation of more realistic 3D plant models for virtual reality applications. Therefore, computer vision may contribute an important share to trends in plant science.…”
Section: Radiometric Calibrationmentioning
confidence: 99%